Tarzan - Buck, Chris; Blessed, Brian, 1937-; Glenn Close; Lance Henriksen; Minnie Driver; Nigel Hawthorne; Wayne Knight; Tony Goldwyn; Lima, Kevin (USA Edgar Rice Burroughs Inc., 1999)
The movie is about the life of Tarzan. Tarzan was a small orphan who was raised by an ape named Kala since he was a child. He believed that this was his family, but on an expedition Jane Porter is rescued by Tarzan. He then finds out that he's human. Now Tarzan must make the decision as to which family he should belong to...
A man raised by gorillas must decide where he really belongs when he discovers he is a human.
Edgar Rice Burroughs
Languages : English
Subtitles : Turkish
Keywords: Adventure; Family; Animation